2016
DOI: 10.1177/0165025416652508
|View full text |Cite
|
Sign up to set email alerts
|

Political socialization of young children in intractable conflicts

Abstract: This article examines the political socialization of young children who live under conditions of intractable conflict. We present four premises: First, we argue that, within the context of intractable conflict, political socialization begins earlier and faster than previously suspected, and is evident among young children. Second, we propose that the agents of political socialization impart narratives of the ethos of conflict and of collective memory in young children that support continuation of the conflict.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 68 publications
1
83
0
1
Order By: Relevance
“…Moreover, this political socialization, despite its lack of uniformity, has a lasting impact on the lives of society members in their adulthood, and thus plays a major role in the dynamics of the intractable conflict due to the powerful nature of this context (Bar-Tal, Diamond, & Nasie, 2015;Cummings et al, 2014). Accordingly, this article examines political socialization in the specific Israeli context of intractable conflict, among Israeli-Jewish young children, providing a number of insights, implications, and consequences.…”
Section: Political Socialization In An Intractable Conflictmentioning
confidence: 99%
“…Moreover, this political socialization, despite its lack of uniformity, has a lasting impact on the lives of society members in their adulthood, and thus plays a major role in the dynamics of the intractable conflict due to the powerful nature of this context (Bar-Tal, Diamond, & Nasie, 2015;Cummings et al, 2014). Accordingly, this article examines political socialization in the specific Israeli context of intractable conflict, among Israeli-Jewish young children, providing a number of insights, implications, and consequences.…”
Section: Political Socialization In An Intractable Conflictmentioning
confidence: 99%
“…A second more motivational explanation has to do with the significance of the category “Arabs” for Jewish Israeli children. Namely, for historical and political reasons, the category is associated with conflict and threat (Bar‐Tal et al, ; Bar‐Tal & Teichman, ). According to coping theories, in a threatening condition, the individual may be especially alert and prone to seek information relevant to the threat, in order to cope with it (Miller, , ), control it (Folkman, ), and reduce the uncertainty attached to it (Berlyne, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, much of what children know about out‐groups is acquired not via direct contact or firsthand experience, but from information they gather from their environment, provided by other people (Degner & Dalege, ; Harris & Koenig, ). This information, however, is often times biased, especially when groups are in conflict (Aboud & Amato, ; Bar‐Tal, Diamond, & Nasie, ; Nasie, Bar‐Tal, & Diamond, ). In fact, even when the bias is implicit in the input, its effect on children's attitudes and beliefs is substantial.…”
Section: Introductionmentioning
confidence: 99%
“…In societies involved in intractable conflict, this process has been demonstrated to begin very early (from age 2–3). It has been suggested that this occurs earlier than in societies not involved in conflict, because life experiences in a conflict accelerate political learning by children (Barrett, ; Bar‐Tal, Diamond, & Nasie, ; Teichman & Bar‐Tal, ). Political socialization in societies in conflicts includes learning and acquisition of conflict‐related concepts and contents which give a general picture of the collective memory of the conflict, its nature, as well as images of the ingroup and of the rival.…”
Section: Introductionmentioning
confidence: 99%